Influence of swimming speed on the affected- and unaffected-arm stroke phases of competitive unilateral arm amputee front crawl swimmers - Osborough, C. D.; Payton, C. J.; Daly, D. J. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Presently, no examination of arm stroke phases has been undertaken for swimmers with a single-arm amputation. It is likely that the roles of their affected- and unaffected-arm within the stroke cycle may differ. Understanding these would be of great practical importance. The aim of this study was to determine if the arm stroke phases used by competitive unilateral arm amputee crawl swimmers differed between their affected and unaffected sides and whether these phases altered with an increase in speed. METHODS: Thirteen (3 male & 10 female) highly-trained swimmers (age 16.9 ± 3.1 yrs) consented to participate. All were elbow level, single-arm amputees. Mean 50 m crawl best time was 32.7 ± 3.1 s. Participants completed five 25 m crawl trials, counterbalanced from slow to maximum swimming speed (SSmax). Trials were video-taped underwater from both sides using tracking camera systems. Three consecutive, non-breathing stroke cycles were analysed. Arm stroke phases for both the unaffected- and affected-arm were determined at 80%, 85%, 90%, 95% and 100% of SSmax. General linear modelling tests were used to compare the changes in arm stroke phases between the affected and unaffected arms across swimming speeds. Statistical significance was set at p < .05. RESULTS: Across swimming speeds, the affected-arm spent relatively longer (p < .05) in all arm stroke phases, with the exception of the Pull phase, compared to the unaffected-arm: Entry and Glide (38.3 ± 9.5% vs. 23.2 ± 8.0%); Pull (10.9 ± 2.8% vs. 23.1 ± 5.9%); Push (18.4 ± 6.4% vs. 13.8 ± 2.7%); Recovery (39.9 ± 3.5% vs. 35.9 ± 3.2%). With increasing speed: 1) the affected-arm`s Entry and Glide phase decreased significantly (p < .05), while the unaffected-arm`s Entry and Glide phase remained unchanged; 2) the unaffected-arm`s Pull phase decreased significantly (p < .05), while the affected-arm`s Pull phase remained unchanged; 3) both arms` Push phase increased significantly (p < .05). DISCUSSION: With an increase in swimming speed the stroke phases of the affected and unaffected arms differed significantly. Such differences might be linked to how these swimmers organised the motor skills necessary to swim crawl. As swimming speed increased the relative durations of certain arm stroke phases changed. The single-arm amputees used a coordination strategy that asymmetrically adjusted their arm movements to maintain the stable repetition of their overall arm stroke cycle when swimming at different speeds.